OPINI AUDIT GOING CONCERN: SINYAL NEGATIF TERHADAP KEBERLANJUTAN OPERASIONAL PERUSAHAAN (STUDI LITERATUR) - Permatasari, Dhini; Oktavia, Reni (Universitas Sangga Buana, 2024)
The continuity of a company needs to be considered and maintained, especially in the midst of economic conditions full of intense competition. Companies will frequently have to contend with divergent interests between shareholders and management when maintaining operational shortages. The most effective way to manage such differences of interest is to hire an auditor. The auditor's role is to measure management performance and verify that financial reports are accurate. Furthermore, evaluating the financial statements' equality, auditors take a company's viability into consideration. The purpose of this study is to understanding the drivers that influence going concern audit opinions while evaluating the continuing company’s operations. The research methodology that uses is literature review. The results of the research demonstrate that debt default, earlier opinions, and audit delay all have an impact on the going concern audit opinions. Furthermore, opinion shopping has no impact on whether going concern audit opinions are accepted.